The relationship between instrinsic motivation and physical activities among students in the Faculty of Education, Seksyen 17 UiTM Shah Alam / Mohamad Adzhari Kamrulzaman - Kamrulzaman, Mohamad Adzhari (2014)
This study is carried out to determine and investigate the factors between intrinsic motivation that influence UiTM students in sport participation. There were 140 respondents involve in this study; they came from Faculty of Education UiTM Shah Alam. Questionnaires were administered randomly in order to obtain information and responses regarding their intrinsic motivation factors. The data collected via the questionnaire was calculated by using SPSS and the findings were tabulated, and then presented in an orderly and easy-to-read manner. The findings ofthis study hold the most factors of intrinsic motivation that influence people to participate in sport activities.